Policy Options for Contributory Health Insurance Schemes in Low and Lower-Middle Income Countries to Enable Progress Towards Universal Health Coverage - Agnes Gatome-Munyua; Joseph Kutzin; Cheryl Cashin (Health Systems & Reform)
The promise of contributory health insurance to generate additional, self-sustaining funding for the health sector has not been achieved in many low- and lower-middle-income countries. Instead, contributory health insurance has been found to exacerbate inequities in access to health care because entitlements are linked to contributions. For these countries with contributory health insurance schemes, with separate institutional arrangements for revenue collection and purchasing, that operate alongside budget-funded and other health financing schemes, it is usually not politically or technically feasible to reverse or eliminate these arrangements even when they fragment the health system. We propose three complementary policy options for countries in this difficult position to enable progress towards UHC: (1) Merge existing schemes into a single scheme (or fewer schemes) to consolidate pooling and purchasing functions. (2) Build on what they have by: reducing reliance on contributions by increasing budget transfers; using existing revenue collection mechanisms to allow the insurance agency to focus on the purchasing function; and strengthening insurance agencies’ operational capacity for purchasing. (3) Reframe the insurance agency’s role within the overall health system, rather than treating it as a distinct system by: unifying data collection and analysis for all patient visits irrespective of scheme membership, and universalizing core benefits across the population. We urge countries to review the patchwork of schemes and avoid worsening fragmentation that compromises health system performance. Countries can then create a strategy to expand coverage more equitably in a sequential manner, while consolidating institutional capacity for purchasing and unifying data systems.